Single-parents and their adolescents' education: call for educational professionalism - K. P., Praharsh; S. A., Rajalakshmi; Kalapatapu, Praveen Kumar; Thangavelu, Asha Priya (Frontiers in Education, 2025)
Adolescents in single-parent families frequently encounter academic challenges amplified by financial, temporal, and emotional constraints. Guided by Family Systems Theory this study explores the lived experiences of single-parents in India and identifies implications for educational professionalism-that is, the capacity of teachers, counselors, and school leaders to respond proactively to diverse family structures. In this study, semi-structured interviews with 12 single-parents of eleven to eighteen year old adolescents were analyzed using reflexive thematic analysis. As a result, five inter-linked themes emerged: (1) challenges of adolescents' academics (Effects of Gadget Addiction on Academic Performance, How Bullying adversely affects Academic Performance, Competitive Curriculum—a major hurdle in the uneven playground of competitive academics); (2) challenges of single-parentship (Financial strain and its adverse effect on academic performance, Responsibility Overload and its adverse impact on academic performance, Adverse effect of Social Stigma and Stereotyping in Academic Performance, Importance of Time management in Academic Performance); (3) communication patterns; (4) emotional wellbeing; and (5) planning and monitoring. These findings underscore the need for flexible, stigma-free school practices, such as after-hours conferences, scholarship pipelines, and anti-bias training to ensure single-parent families are true partners in schooling and implies that embedding these recommendations within professional standards can help operationalize inclusive, context-sensitive education.